2006
DOI: 10.1002/uog.2641
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between three‐dimensional placental volume at 12 weeks and uterine artery impedance/notching at 22 weeks in screening for pregnancy‐induced hypertension, pre‐eclampsia and fetal growth restriction in a low‐risk population

Abstract: Objectives To compare the value of three-dimensional placental volume at 12 weeks and uterine artery Doppler at 22 weeks for predicting pregnancy-induced hypertension (PIH), pre-eclampsia and fetal growth restriction in a low-risk population. Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
92
1
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(102 citation statements)
references
References 18 publications
5
92
1
4
Order By: Relevance
“…In our study, placental volume alone was not a predictor of pre-eclampsia, in contrast to other studies (Hafner et al, 2006;Rizzo et al, 2008). In all our cases PIH was mild and developed at 34 weeks or more, whereas in Hafner et al (2006) and Rizzo et al (2008) there were some cases of severe pre-eclampsia developing before 32 weeks of gestation; in those patients the placental volume was remarkably smaller. Hence, that subgroup of patients with severe pre-eclampsia, which we did not encounter in our study, could explain the disparate findings.…”
Section: Discussioncontrasting
confidence: 96%
See 3 more Smart Citations
“…In our study, placental volume alone was not a predictor of pre-eclampsia, in contrast to other studies (Hafner et al, 2006;Rizzo et al, 2008). In all our cases PIH was mild and developed at 34 weeks or more, whereas in Hafner et al (2006) and Rizzo et al (2008) there were some cases of severe pre-eclampsia developing before 32 weeks of gestation; in those patients the placental volume was remarkably smaller. Hence, that subgroup of patients with severe pre-eclampsia, which we did not encounter in our study, could explain the disparate findings.…”
Section: Discussioncontrasting
confidence: 96%
“…There were no statistically significant differences between the groups with regard to age, gestational age at the examination or delivery, number of the pregnancy or the nuchal translucency measurement. The placental volume was similar between the groups The placental quotient (PQ = placental volume/CRL) was also calculated as suggested by Hafner et al (2001Hafner et al ( , 2006 and was not found to be significantly different between the groups.…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…Importantly, an increasing amount of evidence demonstrates that the neonatal birthweight can be predicted significantly by placental volumetry during early to midpregnancy (Derwig et al 2013) using three dimensional (3-D) sonography (Collins et al 2013;Gassner et al 2003;Metzenbauer et al 2002;Odibo et al 2011;Plasencia et al 2011;Plasencia et al 2012;Rizzo et al 2012). Placental volume deviation might predict chromosomal abnormalities (Gassner et al 2003;Metzenbauer et al 2002), growth retardation (Collins et al 2013;Hafner et al 1998;Hafner et al 2006), late-onset pre-eclampsia (Hafner et al 2006) and other complications during pregnancy (Collins et al 2013;Hafner et al 2006;Odibo et al 2011;Plasencia et al 2011, Plasencia et al 2012Rizzo et al 2012;Salafia et al 2006). …”
Section: Introductionmentioning
confidence: 99%